2019
DOI: 10.1101/763086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annual replication is essential in evaluating the response of the soil microbiome to the genetic modification of maize in different biogeographical regions

Abstract: The importance of geographic location and annual variation on the detection of differences in the rhizomicrobiome caused by the genetic modification of maize (Bt-maize, event MON810) was evaluated at experimental field sites across Europe including Sweden, Denmark, Slovakia and Spain. DNA of the rhizomicrobiome was collected at the maize flowering stage in three consecutive years and analyzed for 20the abundance and diversity of PCR-amplified structural genes of Bacteria, Archaea and Fungi, and functional gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…According to some previous studies, denitrification may sometimes accelerate under Bt crops by promoting nitrite reductase activities along with an increase in denitrifying bacteria (Li et al, 2019;Wu et al, 2004). However, other studies claimed that Bt crops had little to no impact on bacterial nitrite reductases (Szoboszlay et al, 2019). These results were inconsistent with our findings, and the possible explanation can be that we applied glyphosate in the planting of GM soybean in the real scenario, which was not completely consistent with the treatments in the previous studies.…”
Section: Gm Soybean With Glyphosate Application Altered the Dynamicscontrasting
confidence: 99%
“…According to some previous studies, denitrification may sometimes accelerate under Bt crops by promoting nitrite reductase activities along with an increase in denitrifying bacteria (Li et al, 2019;Wu et al, 2004). However, other studies claimed that Bt crops had little to no impact on bacterial nitrite reductases (Szoboszlay et al, 2019). These results were inconsistent with our findings, and the possible explanation can be that we applied glyphosate in the planting of GM soybean in the real scenario, which was not completely consistent with the treatments in the previous studies.…”
Section: Gm Soybean With Glyphosate Application Altered the Dynamicscontrasting
confidence: 99%
“…Calculation of geographic distances were performed using R package geosphere 89 function distGeo with WGS84 ellipsoid. Source tracking was conducted by fast expectation-maximization using FEAST 44 with data from other studies (processed using dada2 following the same parameters as this study) as additional sources/sinks [90][91][92][93][94][95][96] and NCBI BioProject PRJEB42801. For correlation analysis between abiotic and biotic variables the Pearson correlation coefficient for multiple pairwise combinations were calculated using the R package corrplot 97 , with P-value cut-off of 0.05 corrected for multiple tests using Bonferroni correction.…”
Section: Statistical Treatments and Ecological Modellingmentioning
confidence: 99%
“…Calculation of geographic distances were performed using R package geosphere 35 function distGeo with WGS84 ellipsoid. Source tracking was conducted using FEAST 36 with data from other studies (processed using dada2 following the same parameters as this study) as additional sources/sinks [37][38][39][40][41][42][43] and NCBI BioProject PRJEB42801. For correlation analysis between abiotic and biotic variables the Pearson correlation coefficient for multiple pairwise combinations were calculated using the R package Corrplot 44 .…”
Section: Statistical Treatments and Ecological Modellingmentioning
confidence: 99%
“…UV repair and desiccation tolerance 41 . The ability to become aerosolized may vary between taxa in marine 34 and terrestrial 42 systems and so deterministic biotic drivers may also be relevant to recruitment from sources, as well as selective deposition during transit 43 . Overall, the source tracking demonstrated that atmospheric diversity is driven by a complex recruitment process involving local soils plus globally distributed inputs from drylands and the phyllosphere.…”
mentioning
confidence: 99%